Metabolic Conversion of Ceramides in HeLa Cells - A Cholesteryl Phosphocholine Delivery Approach - Kjellberg, Matti A.; Lönnfors, Max; Slotte, J. Peter; Mattjus, Peter (PloS one, 2015)
Ceramides can be delivered to cultured cells without solvents in the form of complexes with cholesteryl phosphocholine. We have analysed the delivery of three different radiolabeled D-erythro-ceramides (C6-Cer, C10-Cer and C16-Cer) to HeLa cells, and followed their metabolism as well as the cell viability. We found that all three ceramides were successfully taken up by HeLa cells when complexed to CholPC in an equimolar ratio, and show that the ceramides show different rates of cellular uptake and metabolic fate. The C6-Cer had the highest incorporation rate, followed by C10-Cer and C16-Cer, respectively. The subsequent effect on cell viability strongly correlated with the rate of incorporation, where C6-Cer had the strongest apoptotic effects. Low-dose (1 μM) treatment with C6-Cer favoured conversion of the precursor to sphingomyelin, whereas higher concentrations (25-100 μM) yielded increased conversion to C6-glucosylceramide. Similar results were obtained for C10-Cer. In the lower-dose C16-Cer experiments, most of the precursor was degraded, whereas at high-dose concentrations the precursor remained un-metabolized. Using this method, we demonstrate that ceramides with different chain lengths clearly exhibit varying rates of cellular uptake. The cellular fate of the externally delivered ceramides are clearly connected to their rate of incorporation and their subsequent effects on cell viability may be in part determined by their chain length.